Communication research to improve engagement with climate change and human health: A review - Campbell, Eryn; Uppalapati, Sri Saahitya; Kotcher, John; Maibach, Edward (Frontiers in Public Health, 2023)
Because of the world's dependence on fossil fuels, climate change and air pollution are profoundly harming both human and planetary health. Fortunately, climate solutions are also health solutions, and they present both local and global opportunities to foster cleaner, healthier, and safer communities. In this review, we briefly discuss the human health harms of climate change, climate and health solutions, and provide a thorough synthesis of social science research on climate and health communication. Through our review, we found that social science research provides an evidence-based foundation for messaging strategies that can build public and political will for climate and health solutions. Specifically, messages that convey the health harms of climate change and highlight the health benefits of climate solutions may be especially effective in building this public and political will. We also found that health professionals are trusted sources of information about climate change, and many have shown interest in engaging with the public and policymakers about the health relevance of climate change and clean energy. Together, the alignment between message strategies and the interest of highly trusted messengers strongly suggests the potential of health students and health professionals to create the conditions necessary to address climate change as a public health imperative. Therefore, our review serves as a resource for those interested in communicating about climate change and health and suggests that social scientists can continue to support practitioners with research and advice on the most effective communication strategies.